The Spectrum of Malignancies among Adult HIV Cohort in Poland between 1995 and 2012: A Retrospective Analysis of 288 Cases - Kowalski, Jacek; Cholewińska, Grażyna; Pyziak-Kowalska, Karolina; Jabłonowska, Elżbieta; Barałkiewicz, Grażyna; Grzeszczuk, Anna; Leszczyszyn-Pynka, Magdalena; Olczak, Anita; Jankowska, Maria; Mikuła, Tomasz; Bociąga-Jasik, Monika; Firląg-Burkacka, Ewa; et al. (Contemporary Oncology/Współczesna Onkologia, 2015)
The aim of the study was to evaluate the spectrum of AIDS-defining malignancies (ADMs) and non-AIDS-defining malignancies (NADMs) in HIV-infected patients in Poland. Material and methods: A retrospective observational study was conducted among HIV-infected adult patients who developed a malignancy between 1995 and 2012 in a Polish cohort. Malignancies were divided into ADMs and NADMs. Non-AIDS-defining malignancies were further categorised as virus-related (NADMs-VR) and unrelated (NADMs-VUR). Epidemiological data was analysed according to demographic data, medical history, and HIV-related information. Results were analysed by OR, EPITools package parameters and Fisher’s exact test. Results : In this study 288 malignancies were discovered. The mean age at diagnosis was 41.25 years (IQR20-81); for ADMs 38.05 years, and for NADMs-VURs 46.42 years; 72.22% were male, 40.28% were co-infected with HCV. The risk behaviours were: 37.85% IDU, 33.33% MSM, and 24.31% heterosexual. Mean CD4+ at the diagnosis was 282 cells/mmł (for ADMs 232 and for NADMs-VUR 395). Average duration of HIV infection at diagnosis was 5.69 years. There were 159 (55.2%) ADMs and 129 (44.8%) NADMs, among whom 58 (44.96%) NADMs-VR and 71 (55.04%) NADMs-VUR. The most frequent malignancies were: NHL (n = 76; 26.39%), KS (n = 49; 17.01%), ICC (n = 34; 11.81%), HD (n = 23; 7.99%), lung cancer (n = 18; 6.25%) and HCC (n = 14; 4.86%). The amount of NADMs, NADMs-VURs in particular, is increasing at present. Male gender (OR = 1.889; 95% CI: 1.104–3.233; p = 0.024), advanced age: 50–60 years (OR = 3.022; 95% CI: 1.359–6.720; p = 0.01) and ≥ 60 years (OR = 15.111; 95% CI: 3.122–73.151; p < 0.001), longer duration of HIV-infection and successful HAART (OR = 2.769; 95% CI: 1.675–4.577; p = 0) were independent predictors of NADMs overall, respectively. Conclusions : In a Polish cohort NHL was the most frequent malignancy among ADMs, whereas HD was the most frequent among NADMs. Increased incidence of NADMs appearing in elderly men with longer duration of HIV-infection and with better virological and immunological control was confirmed. As HIV-infected individuals live longer, better screening strategies, especially for NADMs-VUR, are needed. The spectrum of cancer diagnoses in Poland currently does not appear dissimilar to that observed in other European populations.